Analgesic effects of saikosaponin A in a rat model of chronic inflammatory pain - Lobina, Carla; Lee, Jung Hwan; Pel, Pisey; Chin, Young-Won; Kwon, Hak Cheol; Colombo, Giancarlo (Taylor & Francis, 2023)
Saikosaponin A (SSA) is the main active ingredient of roots of the East Asian medicinal plant, Bupleurum falcatum L. The present study was aimed at delving into the analgesic properties of SSA in a model of chronic inflammatory pain. To this end, rats were initially treated intraplantarly with complete Freund's adjuvant for induction of hyperalgesia. Twenty-four hours later, rats were acutely treated with SSA (0, 1 and 2 mg/kg, i.p.) and exposed to the Von Frey monofilament test or Randall-Selitto paw pressure test for assessment of mechanical hyperalgesia. Treatment with 2 mg/kg SSA had analgesic effects: the nocifensive reaction (paw withdrawal) occurred later and required application of the nociceptive stimulus at a stronger pressure. The analgesic effects of SSA were of magnitude comparable to that of the effects exerted by the reference compound, acetyl salicylic acid (100 mg/kg, i.p.). The well-described anti-inflammatory properties of SSA likely underlie its analgesic effects.